Development of a Da'wah Application for Mental Health Education through Pappasang Messages among the Makassar Community - Yusuf, Yusuf; Wiradinata, Bagas; Hidayah, Ahmad; Zoel Ramadhan, Muhammad; Nafrio, Ahmad; Syamsuardi, Syamsuardi (Ahlussunnah: Journal of Islamic Education, 2023)
In the context of Islamic dakwah, there are various approaches that can be taken, including through dakwah messages and cultural values ​​in a community. As time goes by, the use of media as a means of educating the public is very popular and in great demand today. This research aims to design an application that can be used as a dakwah medium in educating the public through Pappasang messages among the people of Makassar, especially mental health aspects. This research uses the Research and Development method through five steps, namely determining the topic, literature study, discussion, determining the application design to be created, and evaluation. To assess the quality of the product being designed, the author chose two experts in the field of technology and one language and culture expert who understands Pappasang. The application design has seven features as a medium for preaching for mental health, these seven features are Pappasang which contains messages or advice from previous parents about mental health based on Islamic teachings, short story videos about Pappasang, folklore comics, lontara, keywords search Pappasang, prayer, and even groups are available for members to interact with each other and share information about activities on the topic of mental health education. This application is an alternative as a medium for dakwah for mental health among the people of Makassar through Pappasang messages, as well as a means of educating the people of Makassar in recognizing and preserving their culture.